Folk Moral Objectivism: The Case of Harmful Actions - Sousa, Paulo; Allard, Aurélien; Piazza, Jared; Goodwin, Geoffrey P. (Frontiers in Psychology, 2021)
It is controversial whether ordinary people regard beliefs about the wrongness of harmful actions as objectively correct. Our hypothesis, consistent with much of the evidence, is that people are objectivists about harmful actions that are perceived to involve injustice: when two parties disagree about whether such an action is wrong, people think that only one party is correct (the party believing that the action is wrong). However, Sarkissian, Park, Tien, Wright and Knobe (2011) claimed that this evidence is misleading, showing that when the two disagreeing parties are from radically different cultures or species, people tend to think that both parties are correct (a non-objectivist position). We argue that Sarkissian et al.’s studies have a methodological limitation: participants may have assumed that the exotic or alien party had a peculiar understanding of the harmful action, and this assumption, rather than a genuinely non-objectivist stance, may have prompted their increase in non-objectivist responses. Study 1 replicated Sarkissian’s results with additional follow-up measures, which supported our suspicion that their results are inconclusive. Studies 2 and 3 modified Sarkissian’s design to avoid its limitations, and, once the problem was resolved, high rates of objectivism emerged, consistent with our hypothesis that harmful actions are deemed objectively wrong if they are perceived to involve injustice. Studies 4a and 4b targeted our hypothesis more precisely by manipulating perceptions of injustice to see the effect on objectivist responding and by probing the more specific notion of objectivism entailed by our hypothesis. Their results fully supported our hypothesis.